Inhibiting the anaphase promoting complex/cyclosome induces a metaphase arrest and cell death in multiple myeloma cells - Lub, Susanne; Maes, Anke; Maes, Ken; Veirman, Kim De; Bruyne, Elke De; Menu, Eline; Fostier, Karel; Kassambara, Alboukadel; Moreaux, Jérôme; Hose, Dirk; Leleu, Xavier; King, Randall W.; et al. (OncoTarget, 2015)
https://doi.org/10.18632/oncotarget.6768 Susanne Lub, Anke Maes, Ken Maes, Kim De Veirman, Elke De Bruyne, Eline Menu, Karel Fostier, Alboukadel Kassambara, Jérôme Moreaux, Dirk Hose, Xavier Leleu,...
Gesehen am 03.06.2020